2011
DOI: 10.1111/j.1439-0531.2011.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Developmental Potential of Nuclear Transfer Embryos Cloned with Enucleation Methods using Pre‐denuded Bovine Oocytes

Abstract: Enucleation of a recipient oocyte is an important essential process in the procedure of somatic cell nuclear transfer (SCNT). The present study investigated a method for the improvement of enucleation efficiency. Oocytes were denuded of cumulus cells before the completion of nuclear maturation (pre-denuded) after 12 h of culture at MI stage and subsequently cultured for additional 6 h until the completion of nuclear maturation and extrusion of the first polar body (PB1). The extrusion rate of PB1 was not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…In blind enucleation, the removal of metaphase II (MII) chromosomes is usually carried out blindly by aspirating or pushing out the cytoplasm underlying the first polar body (PB1). The rate of successful enucleation by this method is reportedly lower than those of Hoechst staining and chemical treatment [2,3]. On the other hand, enucleation using UV irradiation after staining of the oocyte DNA with Hoechst dye is an efficient and reliable method, but exposure of the recipient oocytes to Hoechst dye and UV irradiation may have detrimental effects on their DNA and cytoplasmic organelles [1,4].…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…In blind enucleation, the removal of metaphase II (MII) chromosomes is usually carried out blindly by aspirating or pushing out the cytoplasm underlying the first polar body (PB1). The rate of successful enucleation by this method is reportedly lower than those of Hoechst staining and chemical treatment [2,3]. On the other hand, enucleation using UV irradiation after staining of the oocyte DNA with Hoechst dye is an efficient and reliable method, but exposure of the recipient oocytes to Hoechst dye and UV irradiation may have detrimental effects on their DNA and cytoplasmic organelles [1,4].…”
mentioning
confidence: 93%
“…In this method, recipient oocytes are denuded of cumulus cells after 12 h of in vitro maturation (IVM) at the metaphase I stage, subsequently cultured for an additional 6 h until nuclear maturation and enucleated [3]. Malenko et al also demonstrated that removal of cumulus cells at 15 h after IVM leads to a high success rate of enucleation [6].…”
mentioning
confidence: 99%
See 3 more Smart Citations